The Influence of Product Quality, Price, and Promotion on Purchasing Decisions on the Shopee Marketplace: (Case Study of Management Students, Faculty of Economics and Business, Mohammad Husni Thamrin University) - Mansur; Fairuzah, Asya Syaqila (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of product quality, price, and promotion on purchasing decisions on the Shopee marketplace. The study was conducted on students of the Management Study Program, Faculty of Economics and Business, Mohammad Husni Thamrin University. The research method used is a quantitative method with a descriptive design by searching for primary data, through questionnaires to respondents after the sampling method. The analysis of this research was carried out using SPSS software. The results of the study indicate that there is a positive and significant influence of product quality variables on purchasing decisions with a calculated t value > t table of 2.100 > 1.991 and a significance value <0.05, namely 0.039. There is a positive and significant influence of price variables on purchasing decisions with a calculated t value > t table of 3.129 > 1.991 and a significance value <0.05, namely 0.002. There is a positive and significant influence of the promotion variable on purchasing decisions with a calculated t value > t table of 2.676 > 1.991 and a significance value <0.05, namely 0.009. Likewise, the variables of product quality, price, and promotion together have a significant influence on purchasing decisions, based on the results of the F test with a calculated F value > F table of 92.890 > 2.72 and a significance value <0.05, namely 0.000. The conclusion of this study is that there is a positive and significant influence between product quality, price, and promotion on purchasing decisions in the Shopee marketplace for Management Study Program students, Faculty of Economics and Business, Mohammad Husni Thamrin University. The coefficient of determination of these variables has an influence of 78.67% while 21.4% is explained by other variables outside this study.